Analisis Produktivitas pada UMKM Dipo Bakery menggunakan Metode Objective Matrix - Golonda, Rahman Hakim; Nugroho, Andung Jati (Innovative: Journal Of Social Science Research, 2024)
UMKM Dipo Bakery Bantul is a food industry that produces white bread and sweet bread located in Bantul Regency, Special Region of Yogyakarta. UMKM Dipo Bakery has a production target of 160,000 pieces per month and produces 3,000 pieces daily. However, in February 2024, UMKM Dipo Bakery encountered difficulties in meeting its production targets due to a malfunctioning dough mixer machine. This issue prompted an observation to identify the factors influencing the decline in production output, thereby providing efforts to improve the factors affecting productivity at the UMKM. The approach utilized is the Objective Matrix (OMAX) method, incorporating criteria such as the productivity of raw materials in this study., labor productivity, machine working hours productivity, and production output productivity. Based on calculations using the Objective Matrix (OMAX) method with the criteria mentioned earlier, productivity of employees received the lowest score of 71, with 14 production processes not reaching productivity targets. Analysis using the fishbone diagram revealed that there are three factors causing the decline in productivity at UMKM Dipo Bakery: human factors, machine factors, and method factors. One of the causes is the inconsistent number of workers and workers not performing according to their skills and expertise. The proposed improvement efforts include creating a list of permanent employees capable of working in areas that match their skills and expertise.